Pelatihan Pembuatan Daftar Pustaka Menggunakan Aplikasi Mendeley - Arafat Febriandirza; Prastika Indriyanti (CV. Multi Kreasi Media, 2025)
Many students struggle with manually creating bibliographies for their academic papers, a crucial step to prevent plagiarism. The Mendeley application offers a solution by automatically generating reference lists, yet not all students are familiar with it. Therefore, an online training session was held via Zoom for the general student population. The goal was to equip them with practical knowledge and skills in using Mendeley, enabling them to manage references independently for various academic writings such as journals and theses. This training is expected to not only enhance individual competencies but also contribute to improving the quality of education in Indonesia.